Pengaruh Eps dan Pertumbuhan Laba terhadap Harga Saham pada sektor Infrastruktur yang tercatat di Bursa Efek Indonesia. Apakah Prioritas Pembangunan Infrastruktur ikut mempengaruhi? - David Subagio; Shany Setiawan; Yulius Christiawan (Business Accounting Review, 2021)
This study was conducted with the aim of knowing whether EPS, profit growth, andinfrastructure development priorities have a positive effect on stock prices (SP) in infrastructuresector companies. In addition, this study also aims to determine the moderating relationshipbetween infrastructure development priorities and the relationship between EPS and profit growthwith stock prices. This research was conducted on 13 infrastructure companies on the IndonesiaStock Exchange (IDX) for the 2010-2019 period. The hypothesis in this study was tested using apanel data regression model. The results of this study found that the EPS variable and the priority ofinfrastructure development are the variables that have the most significant effect on stock prices.This study also found that earnings growth did not have a significant effect on stock prices. Inaddition, this study found that with the policy of prioritizing infrastructure development, therelationship between EPS and stock prices was strengthened. However, this does not apply to therelationship between profit growth and stock prices. The results of this study can be used forinvestors as additional information in making investment decisions.